Communicating the new : - Erwin, Kim (New Jersey wiley, 2014)
Communicating radical innovation is very different from discussing marginal change. Erwin's book provides a serious analysis of why, in this era of VUCA - Volatility, Uncertainty, Complexity and Ambiguity - we need to change our individual and organizational modes of communication. Erwin then provides a series of concrete, practical communication methodologies that we so need. Communicating the New is a book that needs to be offered in all of our best business-school classes.